A note on testing of hypothesis - Singh, Rajesh; Singh, Jayant; Smarandache, Florentin (Italian Journal of Pure and Applied Mathematics, 2011)
In this paper problem of testing of hypothesis is discussed when the samples have been drawn from normal distribution. The study of hypothesis testing is also extended to Bayes set up.